A Juridical Analysis of Clinical Practice by Nurses Without Physician Supervision - I.Manurung; J.Siregar (The Medical Journal of Hospital Management and Health Law, 2026)
Introduction: The shifting dynamics of healthcare delivery have increasingly positioned nurses at the forefront of clinical practice, often leading to situations where they provide medical interventions without direct physician supervision. This study examines the legal implications, professional boundaries, and liabilities arising from independent nursing practices from a juridical perspective. Methods: This research utilizes a normative juridical method, analyzing existing statutory laws, health regulations, judicial precedents, and conceptual legal frameworks governing medical and nursing practices. Results: The findings indicate a critical legal friction between the expanding clinical realities of nursing autonomy and the rigid statutory frameworks that require physician delegation for invasive or diagnostic medical acts. While emergency exceptions exist, prolonged or systematic unsupervised clinical practice by nurses creates significant exposure to administrative, civil, and criminal liabilities due to ambiguous regulatory boundaries. Discussion: The literature underscores that a profound regulatory vacuum exists regarding advanced nursing practices. The intersection of medical law and nursing legislation fails to provide a cohesive shield for practitioners, necessitating a clear distinction between independent nursing care and delegated medical tasks. Bridging this research gap requires establishing precise collaborative protocols to ensure patient safety and legal certainty. Conclusions: Unsupervised clinical practice by nurses without explicit legal authorization or physician delegation constitutes a high legal risk under current frameworks. It is recommended that legislative bodies amend healthcare statutes to formally recognize advanced clinical nursing roles while implementing standardized supervisory guidelines.